Middle East and North Africa Economic Developments and Prospects, October 2013 : Investing in Turbolent Times - World Bank (Washington, DC, 2014)
This report explores the effect of political risk on foreign direct investment (FDI) flows to countries in the Middle East and North Africa. FDI flows dominated capital flows to MENA in the period since the early 2000s and the drop in FDI has been an important component of the economic decline since 2010. The report shows that political turbulence has affected not only the level of FDI flows to the region, but also its composition. It has skewed greenfield FDI, which is the major mode of entry into MENA, towards resource activities that create the least jobs and the non-tradable sectors. At the same time, political shocks have discouraged the high quality greenfield FDI in non-resource tradable manufacturing and services needed for export upgrading and diversification. By hurting these efficiency-seeking investments, shocks to political stability entrench resource dependence and exacerbate the clustering of FDI in the extractive industries and nontradable sectors – a problem associated with the weak business climate and political capture that predate the Arab Spring. Special focus will be needed on reforms that improve competition, transparency, and accountability.